Impact of Chorea on Self-care Activity, Employment, and Health-care Resource Use in Patients with Huntington’s Disease - Daniel O. Claassen; Jonathan DeCourcy; Jennifer Mellor; Charlotte Johnston; Ravi G. Iyer (Journal of Health Economics and Outcomes Research)
**Background:** Chorea is recognized as a prototypic motor feature of Huntington’s disease (HD), but its effect on health-related quality of life (HRQoL) has not been fully explored. This study describes the impact of chorea on HRQoL in patients with HD.